Dissociated Steroids. (2007) - Catley, Matthew C.
Abstract : Glucocorticoids (GCs) are some of the most important drugs in clinical use today. They are mainly used to suppress disease-related inflammation and are widely used for the treatment of many inflammatory diseases including asthma and arthritis. However, GCs are also associated with debilitating side effects that place limitations on the long-term use of these drugs. The development of a GC with reduced side effects would allow more effective treatments for patients who require long-term suppression of inflammation. GCs exert their effects by binding and activating the GC receptor (GR). The activated receptor then binds GC response elements (GREs) in the promoter of genes, and activates transcription (transactivation) or interferes with the activation of transcription by inhibiting the transactivating function of other transcription factors, such as AP-1 and NF-ĸB (transrepression). Transrepression is believed to be responsible for the majority of the beneficial anti-inflammatory effects of GCs, whereas transactivation is believed to play a bigger role in the unwanted side effects of GCs. Compounds that can dissociate the transactivation function of GCs from the transrepression function may, therefore, have an improved therapeutic index. A number of these dissociated corticosteroids have been developed. In vitro assays using these compounds appear to show good dissociation. However, in vivo, the dissociation appears to be lost and these compounds still produce many of the side effects associated with conventional GCs. A better understanding of the molecular mechanisms behind GC-induced effects would allow the design of novel selective GR modulators with an improved therapeutic index.